Synthesis of zeolite A membrane. - Liau, Su Li. (2009)
Zeolite A membrane is designed to separate chemical mixtures with targets of performance that are usually guided by economic consideration, it has been commercially applied to alcohol dehydration and solvent dewatering. The separation performance is determined in terms of membrane permeability and selectivity. The project aims at synthesizing zeolite A membrane and investigating the application of coating a thin gold film on top of the seed layer before secondary growth in controlling the membrane thickness to increase the permeation flux, which is required in practical applications for economical feasibility. Various approaches were investigated and optimized in three main parts; namely crystallization of zeolite A crystals, preparation of pre-treated supports and precursor seed layer and secondary growth of zeolite A seeds into continuous film.. Preliminary experiments prove that the thickness of the synthesized membrane decreases with increasing amount of gold coated on top of the seed layer before secondary growth. Future plans and recommendations are proposed to improve the membrane quality for practical application, by resolving the problems of seed multilayer in seeding and deposition of new crystals from synthesis solution in secondary growth.